Development of nanocrystalline Fe80Cr20 alloy using combination technique of ball milling and ultrasonic treatment for fuel cell interconnector - Feriyanto, Dafit (2014)
Solid Oxide Fuel Cell (SOFC) system consists of anode, cathode, electrolyte and interconnect. This research is focused on interconnect material. The objective of this study is to explore the high energy ball milling (milled) combined with ultrasonic treatment (UT) in obtaining smaller crystallite size, finer surface morphology, higher thermal stability and more homogenous nanocrystalline Fe80Cr20 alloys. This condition was motivated by the previous research that some of the grain growth was observed in a high temperature. At first, this process was carried out by high energy ball milling with milling time of 60 h and later, the samples experienced the ultrasonic treatment with frequency of 35 kHz at various periods of 3 h, 3.5 h, 4 h, 4.5 h, and 5 h. Moreover, it was found that there are no works on these combination treatments (milled and UT). Characterization and analysis were carried out to all samples by using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM) and Energy dispersive X-ray Diffraction (EDS), Thermo Gravimetric Analysis (TGA) and Particle Size Analyzer (PSA). The results showed that the combination treatment samples increases effectively to the solid solubility of Cr to Fe up to 62.1% and decreased the crystallite size up to 2.71 nm at milled and UT 4.5 h sample, these resulted and produces finer surface structure. From EDS results, the combination treatment samples are at suitable composition of 20.05 wt% Cr and 79.95 wt% Fe as compared to other samples. Higher thermal stability was observed on combination treatment sample at 1100 0C up to 12.7 mg or convenient to 63 wt%, 62 wt% and 25 wt% as compared to raw material, UT samples and milled 60 h sample, respectively. The particle size decreased up to 5.23 µm and particle size distribution of combination treatment relatively increased up to 89.57%. It can be concluded that the combination treatment at milled and UT 4.5 h is appropriate to achieve high solid solubility, nano crystallite size, fine surface morphology, high thermal stability and homogenous Fe80Cr20 alloys.